Kuat Tekan Dan Waktu Ikat Beton Abu Terbang Di Air Gambut Dengan Metode Statis Dan Metode Wet-Dry - Zulfario Anugrah Pratama; Monita Olivia; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study examines effect of peat water to the setting time and compressive strength of PCC concrete, and PCC fly ash concrete (PCC-FA). In this study, fly ash was used to replace 25%of weight of cement. This specimen was designed to have the compressive strength of 28 MPa at 28 days. All specimens were cured with two different curing system, static and wet-drysystem. The concrete sample were cured continuously on peat water for 7 and 28 days. While on wet-dry system, the samples were cured by turns wet (soaked on peat water) and dry for 7and 28 days. Peat water had a pH value of 3.0-5.0. The results showed that the addition of fly ash was able to extend the final setting time from 113 minutes to 208 minutes. The compressive strength of PCC (static), PCC-FA (static), and PCC-FA (wet-dry) wereincreased at 28 days immersion in peat water with each increase of 7.24%, 20.45% and 12.89%, respectively. While the compressive strength of PCC concrete (wet-dry) was decreased at 28 days immersion in peat water with a decrease of 4.31%. Based on the test results, it was concluded that the wet-dry cycle adversely affected the concrete strength; however, fly ash addition in the mixture can increase the concrete resistance from the wet-drycycle.Keywords: Fly Ash Concrete, Fly Ash, Wet-Dry, Setting Time, Compressive Strength, Peat Water, PCC